The Effect of Capital Structure on Company Value With Corporate Governance As A Moderating Variable - Oki Ragil Wardana; Tri Gunarsih (Jurnal Ilmu Manajemen & Ekonomika, 2021)
This study aimed to analyze the effect of capital structure on a company's value as a moderating variable and company size as a control variable. The population in this study was a company going public regis-tered with the perception index (CGPI) during 2010-2019. Hypothesis testing is performed using a multi-ple linear regression model moderated regression analysis (MRA). The independent variable in this study is the capital structure. Other variables in the study were moderation variables and company size as control variables. The capital structure is measured by the debt-equity ratio, which compares the company's debt and equity. This study uses a perception index (CGPI) rating published by The Indonesian Institute for (IICG). The size of the company is measured by the natural logarithm of the total assets. The results showed that the capital structure did not affect the value of the company. In contrast, the company's size has a positive and significant effect on the company's value. At the same time, corporate governance weak-ens the relationship of capital structure to the company's value but positively and significantly affects the company's value.